Boldine Attenuates Synaptic Failure and Mitochondrial Deregulation in Cellular Models of Alzheimer’s Disease - Toledo, Juan P.; Fernández-Pérez, Eduardo J.; Ferreira, Ildete L.; Marinho, Daniela; Riffo-Lepe, Nicolas O.; Pineda-Cuevas, Benjamin N.; Pinochet-Pino, Luis F.; Burgos, Carlos F.; Rego, A. Cristina; Aguayo, Luis G. (Frontiers in Neuroscience, 2021)
Alzheimer’s disease (AD) is the most common cause of senile dementia worldwide, characterized by both cognitive and behavioral deficits. Amyloid beta peptide (Aβ) oligomers (AβO) have been found to be responsible for several pathological mechanisms during the development of AD, including altered cellular homeostasis and synaptic function, inevitably leading to cell death. Such AβO deleterious effects provide a way for identifying new molecules with potential anti-AD properties. Available treatments minimally improve AD symptoms and do not extensively target intracellular pathways affected by AβO. Naturally-derived compounds have been proposed as potential modifiers of Aβ-induced neurodysfunction and cytotoxicity based on their availability and chemical diversity. Thus, the aim of this study was to evaluate boldine, an alkaloid derived from the bark and leaves of the Chilean tree Peumus boldus, and its capacity to block some dysfunctional processes caused by AβO. We examined the protective effect of boldine (1-10 M) in primary hippocampal neurons and HT22 hippocampal-derived cell line treated with AβO (24-48 h). We found that boldine interacts with Aβ in silico affecting its aggregation and protecting hippocampal neurons from synaptic failure induced by AβO. Boldine also normalized changes in intracellular Ca2+ levels associated to mitochondria or endoplasmic reticulum in HT22 cells treated with AβO. In addition, boldine completely rescued the decrease in mitochondrial membrane potential (ΔΨm) and the increase in mitochondrial reactive oxygen species, and attenuated AβO-induced decrease in mitochondrial respiration in HT22 hippocampal cells. We conclude that boldine provides neuroprotection in AD models by both direct interactions with Aβ and by preventing oxidative stress and mitochondrial dysfunction. Additional studies are required to evaluate the effect of boldine on cognitive and behavioral deficits induced by Aβ in vivo.